1996
DOI: 10.1080/15216549600201851
|View full text |Cite
|
Sign up to set email alerts
|

Free radical mediated membrane perturbation and inhibition of type‐I iodothyronine 5′‐monodeiodinase activity by lead and cadmium in rat liver homogenate

Abstract: The possible involvement of lipid peroxidation (LPO) in the lead (Pb) and cadmium (Cd) induced thyroid dysfunction with special reference to type‐I iodothyronine 5′‐monodeiodinase (5′‐D) activity was studied in rat liver homogenate. Peroxidative reactions involving membrane components were found to be markedly stimulated by chronic administration of Pb and Cd in rats. Metal induced inhibition in 5′‐D activity was also observed. Since LPO is primarily an outcome of free radical generation, we suggest metal indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…Although the mechanisms for this reduction in BDE-209 metabolites are not well-known, alteration of the capability to metabolize BDE-209, such as through disruption of BDE-209 metabolizing enzymes, could be the main reason. Several studies have demonstrated a role for iodothyronine deiodinase in catalyzing debromination of PBDEs in fish (Browne et al, 2009;Noyes et al, 2011); it may be that Pb can inhibit iodothyronine deiodinase activity via increasing oxidative damage (Chaurasia et al, 1996). Furthermore, iodothyronine deiodinase is a Se-containing enzyme with selenocysteine making up a critical component of the active site of deiodinase (St Germain and Galton, 1997;Köhrle, 2000) and studies indicate that competition between another heavy metal (Cd) and Se (Al-Waeli et al, 2012;El-Sharaky et al, 2007) is a possible mechanism involved in Cd-induced inhibition of iodothyronine deiodinase.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms for this reduction in BDE-209 metabolites are not well-known, alteration of the capability to metabolize BDE-209, such as through disruption of BDE-209 metabolizing enzymes, could be the main reason. Several studies have demonstrated a role for iodothyronine deiodinase in catalyzing debromination of PBDEs in fish (Browne et al, 2009;Noyes et al, 2011); it may be that Pb can inhibit iodothyronine deiodinase activity via increasing oxidative damage (Chaurasia et al, 1996). Furthermore, iodothyronine deiodinase is a Se-containing enzyme with selenocysteine making up a critical component of the active site of deiodinase (St Germain and Galton, 1997;Köhrle, 2000) and studies indicate that competition between another heavy metal (Cd) and Se (Al-Waeli et al, 2012;El-Sharaky et al, 2007) is a possible mechanism involved in Cd-induced inhibition of iodothyronine deiodinase.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the studies suggesting that Cd interferes with the thyroid function at the glandular level, there are fi ndings supporting the effects at the peripheral level by inhibiting the conversion of T4 to T3 (14,(35)(36)(37)(38). Thyroid hormones are metabolised in peripheral tissue by deiodination, conjugation, deamination, and decarboxylation enzyme reactions, and any change in these metabolic pathways may signifi cantly affect thyroid function at the cellular level (35)(36)(37). As deiodination of T4 to T3, which occurs mainly in the liver, depends on 5′-monodeiodinase activity (35,37), hepatic dysfunction is likely to affect thyroid hormone levels (36), T3 in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pilat-Marcinkiewicz et al (16) observed a dose-dependent effect on the structure and function of thyroid follicular cells in rats. Apart from the studies suggesting that Cd interferes with the thyroid function at the glandular level, there are fi ndings supporting the effects at the peripheral level by inhibiting the conversion of T4 to T3 (14,(35)(36)(37)(38). Thyroid hormones are metabolised in peripheral tissue by deiodination, conjugation, deamination, and decarboxylation enzyme reactions, and any change in these metabolic pathways may signifi cantly affect thyroid function at the cellular level (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complementary role in the protection of cells against the detrimental effects of lipid peroxides and free radicals produced during normal metabolism has been postulated for both vitamin E and Se (Rooke et al, 2004). Type I iodothyronine deiodinase, as a membrane bound enzyme (Toyoda et al 1995), is susceptible to lipid peroxidation process (Maiti et al, 1995;Chaurasia et al, 1996; and previous data showed that administration of vitamin E prevents toxic induced thyroid dysfunction, probably through protecting the stability of microsomal membrane in which ID-I exists .…”
Section: Introductionmentioning
confidence: 99%